Pengaruh Persepsi Harga dan Promosi terhadap Keputusan Pembelian Voucher Internet XL di Lamongan - Ina Yulistiowati Astutik, Ina Yulistiowati Astutik; Hery Pudjoprastyono, Hery Pudjoprastyono (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The community now needs the internet in order to have practical access to knowledge and to serve as a channel of communication amongst people. The demand for internet services is rapidly increasing for both informational purposes and for promoting interpersonal interactions. The goal of this study was to determine how perceptions of pricing and promotion affected consumers' choices to buy XL internet vouchers at Bimbi Cell Lamongan. By using a questionnaire to gather data, this study falls under the category of quantitative research. There were 60 respondents in the sample for this study. Purposive sampling was utilized in conjunction with nonprobability sampling as the sampling strategy. data gathered by handing out surveys. With the use of the Smart PLS 3.0 application, the data analysis technique employs Partial Least Square (PLS) analysis. XL online voucher purchases in Lamongan are positively and significantly influenced by price perception and marketing, according to the study's findings. This might be considered significant (positive) since it supports the hypothesis.